2009
DOI: 10.1111/j.1600-0897.2009.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Plasma C3a‐des‐Arg Levels in Women with and without Endometriosis

Abstract: We found no difference in C3a levels between women with and without endometriosis and did not confirm our hypothesis that plasma C3a levels can be used as diagnostic test for endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A recent study reported significantly higher concentrations of C1q, MBL and C1-INH in the peritoneal fluids of EM women as compared to the control group ( 120 ). No difference in plasma C3a levels between women with and without EM was found ( 121 ).…”
Section: Complement In Endometriosis Peritoneal Fluidmentioning
confidence: 99%
“…A recent study reported significantly higher concentrations of C1q, MBL and C1-INH in the peritoneal fluids of EM women as compared to the control group ( 120 ). No difference in plasma C3a levels between women with and without EM was found ( 121 ).…”
Section: Complement In Endometriosis Peritoneal Fluidmentioning
confidence: 99%
“…One study has reported lower levels of C3 and C4 in women with endometriosis, during the follicular phase (Meek et al, 1988). A further study looked at levels of C3a, a proteolytic fragment of the complement pathway that induces inflammatory reactions, but found levels to be similar in infertile women with and without endometriosis (Fassbender et al, 2009). Significant reductions in peripheral mononuclear cell b-endorphin levels have been noted in women with endometriosis, particularly in the luteal phase (Vercellini et al, 1992).…”
Section: Other Immunologymentioning
confidence: 99%
“…Both C4a and C3a levels are predictive of the responses of esophageal cancer patients to chemoradiation (Maher et al, 2011). In more obviously inflammatory disorders, C3a (and to a lesser extent C4a) have been shown to be potentially useful markers in dermatomyositis (Campo et al, 2007), aneurysmal subarachnoid hemorrhage (Mack et al, 2007), acute Lyme disease in tick-bite patients (Shoemaker et al, 2008;Stricker et al, 2009) (Fassbender et al, 2009), adverse pregnancy outcomes (Lynch et al, 2011), chronic obstructive pulmonary disease (Marc et al, 2004;Zhang et al, 2011), cryptogenic and large-vessel disease subtypes of stroke (Stokowska et al, 2011), heart failure (Gombos et al, 2012), cerebral arteriovenous malformations (Haque et al, 2011), asthma (Joks et al, 2008), gestational diabetes mellitus (Lappas, 2011), SLE (Wild et al, 1990), acute relapses in multiple sclerosis (Ingram et al, 2010), IgA nephropathy/Henoch-Schonlein nephritis (Abou-Ragheb et al, 1992) and impaired renal function (Abou-Ragheb et al, 1991), atopic dermatitis (Sergeev Iu et al, 1989), psoriasis (Takematsu et al, 1986) and psoriatic arthritis (Muto et al, 1991), idiopathic pulmonary arterial hypertension (Abdul-Salam et al, 2006), postexercise malaise in myalgic encephalomyelitis/chronic fatigue syndrome (Nijs et al, 2010), AIDS-associated retinitis , and grafted corneas . In addition, C4a and C5a levels decrease after liver resection whereas C3a levels increase (Strey et al, 2009); and C3a and C4a are elevated in liver transplant recipients (Pfeifer et al, 2000).…”
Section: A Complement Peptides Are Important Biomarkers Of Diseasementioning
confidence: 99%